THE INHIBITION OF ACNE PROTEASE BY SOME FLAVONES: DFT, SWISSADMET AND MOLECULAR DOCKING - Latona, Dayo; Taiwo, Abiodun; Asibor, Yemisi; Olarinoye, Funke; Semire, Banjo (Bulletin of Natural Sciences Research, 2024)
This research sought to find a potent drug for the treatment of acne from six (6) flavones. DFT-B3LYP method was used to determine the molecular descriptors like HOMO, LUMO, Dipole moment, and volume of the ligands and standard drugs. SWISSADMET was employed to ascertain the pharmacokinetic properties of the ligands, and molecular docking was achieved by using PyRx and discovery studiosoft wares. It was observed that the six flavones showed better inhibition against acne main protease than the standard drugs, and from the binding affinity results, 5-hydroxy-2-phenylchromen-4-one best inhibited acne protease. The choice of flavones was based on the fact that they have good antibacterial properties because acne thrives in the presence of bacteria.
Keywords: Acne; Flavones; Molecular Docking; Spartan; DFT